A Century of Water–Socioecological Dynamics and Evolutionary Stages in Lake Victoria Basin, East Africa - Zhang, Xinxin; Wang, Mengyuan; Jin, Shiying; Kimirei, Ismael A.; Gao, Qun (MDPI AG, 2025)
Understanding the feedback relationships and evolutionary stages of water–socioecological systems (W-SESs) is crucial for achieving sustainable development in basins. This study focuses on the Lake Victoria Basin (LVB) in East Africa, where population growth, rapid urbanization, and developing industrialization have intensified water resource supply–demand conflicts, leading to socioecological issues such as water environmental degradation and ecological conflicts. The objective of this research is to develop a theoretical framework for the Lake Victoria Basin W-SESs (LVB-WSESs) based on the SES framework, identify the main drivers and critical nodes in the evolution of the LVB-WSESs, analyze the root causes of water–society–ecology conflicts, and explore the feedback relationships and evolutionary stages of the LVB-WSESs over the past century. To achieve this, we employed an integrated qualitative and quantitative analysis of historical data combined with tipping point detection to systematically assess the dynamics of the LVB-WSESs. Our findings show that, under the drivers of climate change (with a 1 °C increase in annual temperature since 1920s), population growth (a six-fold increase since 1920s), economic development, land-use change, urbanization, and species invasion, the basin’s demand for water resources, water environments, and aquatic ecosystems has continually increased, leading to the gradual degradation and imbalance of the basin’s ecological functions. The evolution of the LVB-WSESs can be divided into five stages against the historical backdrop of societal transitions from colonial to independent democratic systems: the stable resource utilization period, the slow environmental change period (1920s–1960s), the rapid environmental imbalance period (1960s–1990s), the transition period from environmental imbalance to protection (1990s–2015), and the reconstruction period of socioecological equilibrium. This study not only enhances understanding of the long-term dynamics of the LVB-WSESs but also provides practical implications for sustainable water management in similar basins globally. It enriches the local practice of global sustainable development theories, providing new theoretical perspectives and case references for future watershed sustainable management. By identifying critical drivers and evolutionary stages, our findings can inform policy decisions and interventions to mitigate socioecological conflicts and achieve basin-level sustainability. Publicly Available Content Database